The Effect of Adaptation of Green Culture on Work Productivity through Turnover Intention in Private Universities in Medan City - Hendry; Syaifuddin; Sofiyan (International Forum of Researchers and Lecturers, 2023)
The main objective of this research is to determine the role of turnover intention in mediating the adaptation of green culture on the work productivity of lecturers at private universities in Medan City. The approach in this research is quantitative. The population comes from 5 private universities in Medan City, totaling 728 students. The sampling technique used cluster sampling, where 258 educational staff were used as research samples. The data analysis technique for this research uses statistical analysis, namely the Partial Least Squares-Structural Equation Model (PLS-SEM), which aims to carry out path analysis with latent variables. The results of data analysis show that the adaptation of green culture directly has a significant effect on employee work productivity. Then, turnover intention hurts employee work productivity. Finally, indirect turnover intention does not significantly mediate the adaptation of green culture on employee work productivity. The implications of the findings in this research show that green cultural adaptation currently needs to be carried out by private universities. The provision of green open space and green cultural values at the private higher education level in Medan City has yet to be consistently and sustainably implemented.